Collected poems - Levinson, Bernard (Hands-On Books, 2020)
Poems from Bernard Levinson's four published collections as well as a new unpublished collection are gathered together into one volume, Collected Poems. Those previously published collections are From Breakfast to Madness (Ravan Press 1974); Welcome to the Circus (Justified Press 1991); I See You (Southern College Publishers 2001) and I Dreamt I Was Flying (Nimrod Publishers 2007).